The determinants of information sharing and the performance of supply chain: A case of beverage manufacturing companies in Dar es salaam, Tanzania - Kabelele, Deus P (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for the Degree of Masters of Science in Procurement and Supply Chain Management of Mzumbe University